2002
DOI: 10.1034/j.1399-0004.2002.610407.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy in congenital complete lipodystrophy

Abstract: Molecular genetic studies have pointed to a relationship between congenital lipodystrophy syndromes and some cardiac disorders. For instance, mutations in LMNA cause either lipodystrophy or cardiomyopathy, indicating that different mutations in the same gene can produce these clinical syndromes. The present authors describe a 10-year-old female with Berardinelli-Seip congenital complete lipodystrophy (MIM 606158) caused by homozygosity for a frameshift mutation in BSCL2. In addition to the typical attributes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 27 publications
0
56
1
4
Order By: Relevance
“…Another finding that differed from the literature 8,11,15,38,39 was the presence of systolic dysfunction. Only 1 patient in this study had left ventricular systolic dysfunction.…”
Section: Insulin Resistance and Cardiopathiescontrasting
confidence: 53%
See 1 more Smart Citation
“…Another finding that differed from the literature 8,11,15,38,39 was the presence of systolic dysfunction. Only 1 patient in this study had left ventricular systolic dysfunction.…”
Section: Insulin Resistance and Cardiopathiescontrasting
confidence: 53%
“…Despite the low mean age (22.4% ± 9.7 years) of these patients, 54.6% exhibited ventricular ectopic beats with CLVH present, and another 54.6% with CLVH absent (table 5). There is only one report in the literature: a 5-year-old patient, who was monitored for 24 hours, showing normal Holter 38 .…”
Section: Insulin Resistance and Cardiopathiesmentioning
confidence: 99%
“…Cardiac involvement in CGL has been reported in the literature [9][10][11][12][13][14][15] but there are no cases describing early onset cardiac failure, as in our case. Bjornstad et al [9] reported 6 cases of BSCL presenting myocardial hypertrophy, and Rheuban et al [10] described 4 other similar cases.…”
Section: Discussionmentioning
confidence: 67%
“…The average age at diagnosis in Bjornstad's series, confirmed by Rheuban was 20 years. A single case with an early onset hypertrophic cardiomyopathy has been reported in a Portuguese child who had evidence of ventricular hypertrophy at the age of 6 months, but she was not symptomatic until the age of 10 years [11]. The mechanism causing hypertrophic cardiomyopathy in patients with genetic insulin resistance syndrome as BSCL, and therefore with hyperinsulinemia, may result from the insulin action in the receptors of Insulin-like growth factor I (IGF-1) present in the myocardial tissue [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…In normal conditions TG are stored only in adipocytes, under the control of PPAR with minimal presence of lipids in other tissues [231,232]; in this way adipocytes play indirectly a key role in the control of systemic glucose, lipid homeostasis and insulin sensitivity through the regulation of the serum level of FFA. In congenital lipodystrophy, a disease characterized by a decreased capacity of lipid storage in adipose tissue, the non-adipose organs accumulate TG and there is a premature cardiomyopathy [233]. When an overload of cellular FFA takes place caused by increased lipolysis or increased uptake (evident in clinical settings as in diabetes, in the experimental CD36 and LPL overexpression [234,235] or in settings of reduced FAO), lipid deposits in the myocardium and other organs may occur giving rise to the already seen phenomenon of lipotoxicity [236].…”
Section: Cardiac Lipotoxicity In Chronic Heart Failure and Sepsismentioning
confidence: 99%